2015
DOI: 10.1089/ars.2014.6186
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide Maintains Mitochondrial DNA Replication via Demethylation of TFAM

Abstract: Aims: Hydrogen sulfide (H 2 S) exerts a wide range of actions in the body, especially in the modulation of mitochondrial functions. The normal replication of mitochondrial DNA (mtDNA) is critical for cellular energy metabolism and mitochondrial biogenesis. The aim of this study was to investigate whether H 2 S affects mtDNA replication and the underlying mechanisms. We hypothesize that H 2 S maintains mtDNA copy number via inhibition of Dnmt3a transcription and TFAM promoter methylation. Results: Here, we demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 53 publications
1
38
0
Order By: Relevance
“…Using a recently developed mitochondrial-specific H 2 S donor, AP3930, we have shown previously that mitochondria-specific H 2 S delivery significantly reduces amount of mtDNA damaged induced by oxidative stress in cultured endothelial cells, suggesting a stimulatory role of H 2 S in process of the mtDNA repair16. Another report demonstrated that cells deficient in H 2 S production (due to CSE deficiency), have reduced number of mtDNA copies42. Thus - although a correlation between H 2 S and mtDNA damage/repair has been implicated - the molecular mechanisms of how H 2 S regulates the integrity of the mtDNA, and how these processes are important for the tumorigenic potential of cancer cells is currently unknown.…”
Section: Discussionmentioning
confidence: 96%
“…Using a recently developed mitochondrial-specific H 2 S donor, AP3930, we have shown previously that mitochondria-specific H 2 S delivery significantly reduces amount of mtDNA damaged induced by oxidative stress in cultured endothelial cells, suggesting a stimulatory role of H 2 S in process of the mtDNA repair16. Another report demonstrated that cells deficient in H 2 S production (due to CSE deficiency), have reduced number of mtDNA copies42. Thus - although a correlation between H 2 S and mtDNA damage/repair has been implicated - the molecular mechanisms of how H 2 S regulates the integrity of the mtDNA, and how these processes are important for the tumorigenic potential of cancer cells is currently unknown.…”
Section: Discussionmentioning
confidence: 96%
“…More specifically, exogenous H2S improved mtDNA copy number and increased TFAM expression. H2S functions to diminish DNA methlytransferase 3a (DNMT3a) resulting in TFAM demethylation, it also sulfhydrates interferon regulatory factor 1 (IRF-1) which increases the binding of IRF-1 to the DNMT3a promoter [45]. These treatment methods target TFAM’s regulation over mtDNA copy number [1].…”
Section: Mitochondrial Transcription Factor a (Tfam)mentioning
confidence: 99%
“…Supply of H 2 S-releasing compounds rescued these cells from the harmful effects of high levels of circulatory homocysteine [123, 124]. Hydrogen sulfide alters the epigenetics of the mitochondrial genome, contributing to the replication of mitochondrial DNA, cellular energy metabolism and mitochondrial bioenergetics [125]. Exogenous H 2 S repressed the expression of DNA methyltransferase in cultured smooth muscle cells and aortic tissues from mice, resulting in the demethylation of certain regions of the mitochondrial genome, whereas CSE deficiencies showed opposite effects [125].…”
Section: Hydrogen Sulfide and Agingmentioning
confidence: 99%